Anti-MDA5+ dermatomyositis following SARS-COV-2 infections: a systematic review - Lattarulo, Simone; Centrone, Francesca; Chironna, Maria (Frontiers in Immunology, 2025)
BackgroundAnti-MDA5+ dermatomyositis (DM), also called anti-MDA5+ syndrome, or clinically amyopathic dermatomyositis (CADM), is characterized by extra-muscular DM manifestations such as skin rash, arthralgia, and rapid progressive-interstitial lung disease. Between 2020 and 2024, an increase in serum titer of anti-MDA5 autoantibodies (AABs) and MDA5+ DM cases was registered among the general population. Given the role of MDA5 as a viral-RNA sensor, it is considered a key molecule in rheumatological disorders, as studies show its activity is triggered by viral infection. Here, we conducted a systematic review of studies reporting an unambiguous temporal link between SARS-CoV-2 infections and development of MDA5+ DM. The aim was to clarify our understanding of this idiopathic rheumatic nature.MethodsThis review meets Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines (PRISMA). The Google Scholar, PubMed, Scopus and ScienceDirect were searched using appropriate keywords to identify relevant studies published from 2020–2025. Twenty-nine studies concerning the development of MDA5+ DM in COVID-19 patients, as well as molecular pathogenetic mechanisms and pharmaceutical treatments were included.ResultsAnti-MDA5 antibodies have been detected in patients with COVID-19, as well as in sera from post-COVID patients, and their presence correlates positively with disease severity. The onset of MDA5+ DM, in different phenotypic variants, increased during the COVID-19 pandemic, paralleled by an increase in the incidence of juvenile idiopathic inflammatory myopathies (JIIM). The literature here reported shows that MDA5+ DM arises after primary SARS-CoV-2 infection, which could stimulate an antiviral pathway overactivation, leading to innate and adaptive immune cells recruiting, cytokine storm, and synthesis of autoantibodies.ConclusionThis review provides evidence for a link between primary SARS-CoV-2 infections, anti-MDA5 AABs synthesis and emergence of MDA5+ DM in phenotypically different variants such as MIP-C, driven by the virus’s inclination to trigger type-I interferonopathy in genetically predisposed individuals.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier 1129317.